Stock market reactions to COVID-19: Evidence from Morocco - JANNDI, Widad; MOUSSAMIR , Abdelhak (Revue Internationale des Sciences de Gestion, 2021)
The COVID-19 pandemic weakened the global economy, halting many economic activities and causing a rapid and sharp drop in demand and employment. Consequently, global stock market prices experienced their worst drop since the 2008 financial crisis. In Morocco, the Casablanca Stock Exchange (CSE) started the year 2020 in good shape but was severely affected by the pandemic in March with its two main indices Masi and Madex plunging by 20.85% and 21.26% to 9,704.85 and 7,876.80 points respectively. This study examines in detail the impact of the COVID-19 pandemic on CSE using daily data and the event study method. The results indicate abnormal returns for 13 industries of which two reacted positively and 11 responded negatively. The Banking industry is found to be the hardest hit sector with a 20.79% reduction during the event date followed by the Materials, Software and Computer Services sector. In contrast, shares of the Telecommunication industry realized a surge of 4.38%. The variables and parameters contributing to these reactions are explained.